Field and Numerical Investigation to Determine the Impact of Environmental and Wheel Loads on Flexible Pavement - Bayat, Alireza (University of Waterloo, 2009)
There is a growing interest for the use of mechanistic procedures and analytical methods in the design and evaluation of pavement structure rather than empirical design procedures. The mechanistic procedures rely on predicting pavement response under traffic and environmental loading (i.e., stress, strain, and deflection) and relating these responses to pavement field performance. A research program has been developed at the Center for Pavement and Transportation Technology (CPATT) test track to investigate the impact of traffic and environmental parameters on flexible pavement response. This unique facility, located in a climate with seasonal freeze/thaw events, is equipped with an internet accessible data acquisition system capable of reading and recording sensors using a high sampling rate. A series of controlled loading tests were performed to investigate pavement dynamic response due to various loading configurations. Environmental factors and pavement performance were monitored over a two-year period. Analyses were performed using the two dimensional program MichPave to predict pavement responses. The dynamic modulus test was chosen to determine viscoelastic properties of Hot Mix Asphalt (HMA) material. A three-step procedure was implemented to simplify the incorporation of laboratory determined viscoelastic properties of HMA into the finite element (FE) model. The FE model predictions were compared with field measured pavement response. Field test results showed that pavement fully recovers after each wheel pass. Wheel wander and asphalt mid-depth temperature changes were found to have significant impact on asphalt longitudinal strain. Wheel wander of 16 cm reduced asphalt longitudinal strains by 36 percent and daily temperature fluctuations can double the asphalt longitudinal strain. Results from laboratory dynamic modulus tests found that Hot Laid 3 (HL3) dynamic modulus is an exponential function of the test temperature when loading frequency is constant, and that the HL3 dynamic modulus is a non-linear function of the loading frequency when the test temperature is constant. Results from field controlled wheel load tests found that HL3 asphalt longitudinal strain is an exponential function of asphalt mid-depth temperature when the truck speed and wheel loading are constant. This indicated that the laboratory measured dynamic modulus is inversely proportional to the field measured asphalt longitudinal strain. Results from MichPave finite element program demonstrated that a good agreement between field measured asphalt longitudinal strain and MichPave prediction exists when field represented dynamic modulus is used as HMA properties. Results from environmental monitoring found that soil moisture content and subgrade resilient modulus changes in the pavement structure have a strong correlation and can be divided into three distinct Seasonal Zones. Temperature data showed that the pavement structure went through several freeze-thaw cycles during the winter months. Daily asphalt longitudinal strain fluctuations were found to be correlated with daily temperature changes and asphalt longitudinal strain fluctuations as high as 650m/m were recorded. The accumulation of irrecoverable asphalt longitudinal strain was observed during spring and summer months and irrecoverable asphalt longitudinal strain as high as 2338m/m was recorded.
Keywords: Pavement Response; Instrumentation; Flexible Pavement; Environmental Loads; Wheel Loads; Pavement Performance; Civil Engineering